Therapeutic Hypothermia in improving Neurological outcome after Cardiac Arrest - Darine Ashraf Soudy (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2018)
Background: Only a few patients survive cardiac arrest as it with widespread cerebral ischemia frequently leads to severe neurologic impairment.  Aim: Our objective was to evaluate whether induced hypothermia improves neurologic recovery in survivors of primary cardiac arrest or not.  Methods: We included randomized or quasi-randomized, recent controlled trials (from 2002 till now based on the electronic databases of PubMed/Medline, Scopus, and Cochrane were searched for relevant literature and studies of adults who were successfully resuscitated, where therapeutic hypothermia (TH) was applied within 6 hours after arrival at emergency department after sudden cardiac arrest especially when asphyxia is the cause of the arrest and where neurologic outcome was compared with no history of previous cardiac arrest. We excluded studies without a control group and historical researches.  Result: In patients who have been successfully resuscitated after cardiac arrest due to ventricular fibrillation, therapeutic mild hypothermia increased the rate of a favorable neurologic outcome and reduced mortality.  Conclusion: Mild resuscitative hypothermia in patients is feasible and safe. It improves short term neurologic recovery and survival in patients resuscitated from cardiac arrest of presumed cardiac origin. Its long-term effectiveness and feasibility at an organizational level need further research.